Pengaruh Brand Image terhadap Purchase Intention Produk iPhone dengan Perceived Quality dan Trust sebagai Variabel Mediasi - Ni Nyoman Raditya Juli Widiantari; Nilna Muna; Ida Ayu Oka Martini; Putu Ayu Titha Paramita Pika (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
The objective of the research is to investigate how brand image affects the purchase intention of iPhone products towards considering perceived quality and trust as intervening variables. A quantitative method was used to gather data from 200 iPhone users or potential buyers in Bali, and the data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that the brand image has no direct impact on purchase intention, which means that a strong brand image is not enough to persuade consumers to buy luxury products. Nonetheless, brand image plays an important role in the customers' cognitive and affective evaluations as it significantly affects perceived quality and trust. Perceived quality takes the lead among the factors with a direct effect on purchase intention, while trust comes next, which implies that the customers' intention to buy iPhone products is primarily motivated by their perception of product performance, features, reliability, and security. The roles of perceived quality and trust as mediators between the brand image and purchase intention are significant. Thus, the research brings to light thatmarketers dealing with premium technology products like the iPhone need to work on the perceived product quality and consumer trust to turn the intention to purchase into reality.